2016
DOI: 10.5414/cn108497
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a kidney stress test to evaluate renal functional reserve

Abstract: We found no difference between 1 and 2 g/kg body weight PL to elicit sGFR. RST may be useful to predict susceptibility and risk of developing acute kidney injury and/or progression to chronic kidney disease. RST uncovers the possible loss of renal functional mass when this condition is not manifested clinically. Further studies are needed to set this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 0 publications
1
49
1
Order By: Relevance
“…This introduces the concept of a patient-centered 'precision' approach to CRRT prescription. This would imply that CRRT dose would be modified over time to match the clinical demands of the patient (i.e., changes to kidney reserve, changes to illness severity, changes to non-renal organ dysfunction, changes to fluid balance and metabolic status) [33] . This would be analogous to how mechanical ventilation is prescribed in critically ill patients with acute lung injury.…”
Section: Contextmentioning
confidence: 99%
“…This introduces the concept of a patient-centered 'precision' approach to CRRT prescription. This would imply that CRRT dose would be modified over time to match the clinical demands of the patient (i.e., changes to kidney reserve, changes to illness severity, changes to non-renal organ dysfunction, changes to fluid balance and metabolic status) [33] . This would be analogous to how mechanical ventilation is prescribed in critically ill patients with acute lung injury.…”
Section: Contextmentioning
confidence: 99%
“…Old technique of kidney stress test, which is forgotten for a long-time, despite its simplicity, it can adequately reflect the condition of intraglomerular hemodynamic and can easily realizable in clinical practice. 21 Many studies demonstrated response of basal GFR to different stimuli from usual chicken and beef meat intake to amino acid and some drugs infusions in healthy individuals. 8,9,[22][23][24][25][26] In our study we first used …”
Section: Discussionmentioning
confidence: 99%
“…Recent data from our group suggest that a protein-loading test with 1 g/kg of body weight is a sufficient stimulus to elicit the maximum GFR. The resultant sGFR is thought to adequately quantify the global renal capacity [41] . In our study, the sGFR before transplant does not result statistically different from the cumulative sGFR obtained in donors and recipients after transplant ( p = 0.73; Fig.…”
Section: Discussionmentioning
confidence: 99%